PENYUSUNAN DOKUMEN STANDARD OPERATING PROCEDURE (SOP) DALAM UPAYA PENINGKATAN KUALITAS PROSES PRODUKSI DONAT DI DONKEN MOJOKERTO - Zenita Afifah Fitriyani (Universitas Tribhuwana Tunggadewi, 2020)
The objective of this research is to compile a Standard Operating Procedure (SOP) for doughnut production process at Donken Mojokerto. The benefit of this research is to help Donken Mojokerto in improving their production process with the compiled SOP, so that it can be considered to be a guidance to perform the production process. The steps of the research process are: Problems identification, collecting data through observation, interview, literary studies, and questionnaire. Then compiling the SOP document, revising SOP document to the employees and validation to the employer. Standard Operating Procedure of doughnut production process consists of seven steps, those steps are: Providing material, each material’s weight and its composition should be match with the formula or the recipe that has been determined. Dough making, the first dough mixing process were consist of wheat flour, sugar, egg, yeast, water, baking powder, and calcium. Then those materials were mixed using an electric mixer for about twenty minutes. Next, add butter and salt then remixed for about five minutes until it becomes dense. Dough isolation process, leave the dough for about 25 minutes until it puffed up. Molding process, the dough were divided into four to make the molding process easier, then thin it down using a rolling pin and reversible sheeter until 0.5 cm of thickness, and then shaped using a manual mold. Frying process, the already shaped dough were leaved for 30 minutes and then fried in a 1820-1900C oil on a frying pan for two minutes. Draining process, the well-fried doughnuts were drained on a rack for ten minutes. Topping process, the chocolate flakes, melt chocolate, butternut, cream, or cheese topping were added to the upside of the doughnut.